Study on Impact of Low Load to Frictional Coefficient of Silicon – Silicon Couple in MEMS Devices - Phan, Van Manh; Nguyen, Truong Sinh; Pham, Hong Phuc (Old Journal, 2017)
The paper proposes the experimental process to determine the impact of low load to frictional coefficient of silicon – silicon couple by pin on disk model. The first experiment was performed with range of contact load from 2 mN to 30 mN. The coefficient of friction (COF) of Si – Si couple varies from 0.15 to 0.16 and are considered to be constant and the COF of SiO2 – SiO2 couple changes from 0.35 to 0.24. When increasing the surface roughness, the COF of SiO2 – SiO2 couple changes from 0.15 to 0.30. Consequently, the impact of surface force on frictional properties of materials have to be involved during the prediction of potential behavior of materials. The impact of surface roughness and different frictional behaviors of silicon between low and normal load are also mentioned in the second experiment.